Radiative properties and QPOs around charged black hole in Kalb–Ramond gravity - Shokhzod Jumaniyozov; Muhammad Zahid; Mirzabek Alloqulov; Inomjon Ibragimov; Javlon Rayimbaev; Sardor Murodov (European Physical Journal C: Particles and Fields)
Abstract Studies of accretion disc luminosities and quasiperiodic oscillations around black holes may help us understand the gravitational properties of black hole spacetime. This work is devoted to studying the radiation properties of the accretion disk around the black holes in Kalb–Ramond gravity. We investigate the event horizon of the black hole spacetime and calculate the effective gravitational mass of the spacetime. Also, we analyze the circular motion of test particles in the black hole spacetime. The effects of the black hole charge and KR parameters on the particles’ effective mass, energy, and angular momentum at circular orbits and innermost stable circular orbits are studied. The frequency of Keplerian orbits and the radial and vertical oscillations of the particles along stable orbits are calculated and applied to analyze the existence of QPO in relativistic precession, warped disc, and epicyclic resonance models. QPO orbits’ locations with ratios of upper and lower frequencies of twin-peaked QPOs 3:2, 4:3, and 5:4 are analyzed compared to ISCO. We also obtain constrain values for the black hole mass, charge, KR field parameter, and QPO orbits found using Markovian chain Monte Carlo (MCMC) simulations for stellar mass (XTE J1550, GRS 1915+105), intermediate mass (M82-X1), and supermassive black holes (Sgr A*). Finally, we explore the radiative properties of the accretion disk around the charged black hole in KR gravity, such as the total radiation flux, accretion disc temperature, and differential luminosity.